KEBERLANJUTAN USAHATANI BAWANG MERAH DESA SUNGAI GERINGGING KECAMATAN KAMPAR KIRI KABUPATEN KAMPAR PROVINSI RIAU - Sri Ayu Kurniati (UIR Press, 2019)
ABSTRACT The way farmers assess the perception of the sustainability of shallot farming will help the government to implement it at the farm level. This research aims to analyze the characteristics of shallot farmers, the perception of farmers on sustainable agriculture, and the relationship between the characteristics of onion farmers with the perception of sustainable development. The location was selected purposively with a reason that Geringging River Village is the initial place for planting shallots in Kampar District which was conducted by 40 farmers. Data were analyzed statistically using a Likert and Chi-Square scale. The results showed that the characteristics of the farmers are productive age, low education level, 2.3 years of farming experience, and the number of dependents of 5 families. The farmers had access to extension workers so that sources of knowledge about sustainable agriculture are obtained from extension staffs. In the economic dimension, the important variables actively cultivate shallot farming and use the high quality of red onion seeds. In the social dimension, there are 6 variables that have very important categories. While the environmental dimension is only variable using proper irrigation water is considered very important. The level of education and sources of knowledge about agriculture had a significant relation to farmers' perceptions of sustainable agriculture. This indicated that sustainable agriculture requires a sufficient level of education, adequate knowledge and a clear source of knowledge.